Fremdkörper im Bronchialsystem - Herth, Felix (HNO, 2012)
Coughing, wheezing, dyspnea and recurrent pneumonia can be signs of foreign body aspiration. About 80% of all foreign body aspirations occur in children, especially in infants between 1 and 3 years of age. Although most foreign bodies are found in the bronchi they are especially dangerous in the larynx or trachea. Foreign body aspiration is less common in adults, being confirmed in only about 1-2 of every 1,000 bronchoscopies. The most common foreign bodies are foods particles. Bronchoscopy is the method of choice for foreign body removal.